A comparative-descriptive study of extreme value distributions using the extreme value VaR and crash option valuations on the Philippine stock market index from 1986 to 2006 - Reporen, Ruth-Ann G. (Animo Repository, 2007)
Assessing the Value at Risk of extreme events such as a stock market crash has been an important issue in the risk management of financial portfolios. Extreme Value Theory has provided the solid fundamentals needed for the statistical modeling of such events. Market crashes and other periods of high volatility have created the need for a worldwide adoption of financial innovation and this has offered considerable challenge to financial engineers. This study described and compared the three extreme value distributions (Weibull, Gumbel and Fréchet distributions) using the Generalized Extreme Value approach to Value at Risk. Using the daily returns of the Philippine stock market index from 1986 to 2006 that covered a total of 5,476 trading days, the proponent investigated the behavior of extreme value distributions at different levels of confidence. This study was the first attempt to apply crash option valuations in the Philippine Stock Market. Using the Black-Scholes Option Pricing Theory, the proponent integrated the estimated extreme volatilities in the model to examine the premiums and payoffs incorporated in the product. Custom tailored Over-the-Counter options were considered since no organized exchange has existed yet in the market. Extensions of the model led to the assessment of more sophisticated crash options. Exotic options considered were the Lookback Put Option and the Cash-or-Nothing Digital Put Option. Finally, the study presented various illustrative examples including the application of the model on a Philippine Equity Mutual Fund.